2015
DOI: 10.3390/ijerph121012110
|View full text |Cite
|
Sign up to set email alerts
|

Residential Radon Exposure and Incidence of Childhood Lymphoma in Texas, 1995–2011

Abstract: There is warranted interest in assessing the association between residential radon exposure and the risk of childhood cancer. We sought to evaluate the association between residential radon exposure and the incidence of childhood lymphoma in Texas. The Texas Cancer Registry (n = 2147) provided case information for the period 1995–2011. Denominator data were obtained from the United States Census. Regional arithmetic mean radon concentrations were obtained from the Texas Indoor Radon Survey and linked to reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
1
14
1
Order By: Relevance
“…Our choice balances the ideas that, in a positively skewed distribution (like a lognormal distribution), the median, and to some degree the mean, may underrepresent the true potential hazard; conversely, a higher percentile (e.g., the 95th or 99th percentile) likely overestimates the potential hazard in most cases. Our choice is also consistent with studies that have found the 75th percentile to be a useful statistic to represent risk in analyses of relationships between radon and lung cancer (Jones, 1995), radon and childhood lymphoma (Peckham et al, 2015), air pollution and placental abruption (Kioumourtzoglou et al, 2019), gestational diabetes and abdominal circumference (Kjos & Schaefer‐Graf, 2007), and mercury exposure in rural mining towns (Ohlander et al, 2013).…”
Section: Resultssupporting
confidence: 79%
“…Our choice balances the ideas that, in a positively skewed distribution (like a lognormal distribution), the median, and to some degree the mean, may underrepresent the true potential hazard; conversely, a higher percentile (e.g., the 95th or 99th percentile) likely overestimates the potential hazard in most cases. Our choice is also consistent with studies that have found the 75th percentile to be a useful statistic to represent risk in analyses of relationships between radon and lung cancer (Jones, 1995), radon and childhood lymphoma (Peckham et al, 2015), air pollution and placental abruption (Kioumourtzoglou et al, 2019), gestational diabetes and abdominal circumference (Kjos & Schaefer‐Graf, 2007), and mercury exposure in rural mining towns (Ohlander et al, 2013).…”
Section: Resultssupporting
confidence: 79%
“…To the best of our knowledge, this is the first study to show a significant NHL risk in female children and adolescents in association with indoor radon exposure. The increased risk of NHL in females was likely due to the risk in children and adolescents in the present study, which is not consistent with the previous reports that showed no clear association with NHL in children and adolescents [ 32 , 40 ]. However, these previous studies did not stratify their analysis by gender.…”
Section: Discussioncontrasting
confidence: 99%
“…This is based on the information that the youngest controls whose individual chronic exposure to radon is having increased oxidative stress on the bone marrow stem cells, causing telomere length shortening [ 31 , 32 , 33 ]. Therefore, short telomere has a correlation with lung cancer risk and leukemia in high residential radon exposure and the association is modulated by age and the cumulative lifetime exposure to radon [ 13 , 34 , 35 ]. Significantly, future larger studies are needed to entail the in-depth analysis of underlying mechanism of the age differences in the association between telomere length and lung cancer risk with respect to high level of natural radiation background areas.…”
Section: Resultsmentioning
confidence: 99%